2020
DOI: 10.1152/ajpgi.00255.2019
|View full text |Cite
|
Sign up to set email alerts
|

Sacral nerve stimulation increases gastric accommodation in rats: a spinal afferent and vagal efferent pathway

Abstract: Impaired gastric accommodation (GA) has been frequently reported in various gastrointestinal diseases. No standard treatment strategy is available for treating impaired GA. We explored the possible effect of sacral nerve stimulation (SNS) on GA and discovered a spinal afferent and vagal efferent mechanism in rats. Sprague-Dawley rats (450–500 g) with a chronically implanted gastric cannula and ECG electrodes were studied in a series of sessions to study: 1) the effects of SNS with different parameters on gastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…We speculated that this might be attributed to (a) possible innervation of the vagus nerve to the rectum and/or (b) a possible vagal afferent and sacral efferent pathway. In a few recent studies, sacral nerve stimulation was reported to alter functions of the gastrointestinal organs (stomach and small intestine) that are not innervated with the sacral nerve ( 77 , 78 ), and a spinal afferent and vagal efferent pathway was indicated with the sacral nerve stimulation ( 79 ).…”
Section: Discussionmentioning
confidence: 99%
“…We speculated that this might be attributed to (a) possible innervation of the vagus nerve to the rectum and/or (b) a possible vagal afferent and sacral efferent pathway. In a few recent studies, sacral nerve stimulation was reported to alter functions of the gastrointestinal organs (stomach and small intestine) that are not innervated with the sacral nerve ( 77 , 78 ), and a spinal afferent and vagal efferent pathway was indicated with the sacral nerve stimulation ( 79 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since the vagus and sacral nerves contain both the afferent and efferent parasympathetic fibers, the antiinflammatory effect of VNS and SNS could be due to either a direct activation of these parasympathetic efferents and/or the activation of the parasympathetic afferents projecting to the brainstem parasympathetic control centers and resulting in activation of the vagal and sacral efferents. [96,97] Moreover, the vagosympathetic reflex has been proposed, where the abdominal vagal efferents in the celiac ganglion activate the sympathetic efferents in the greater splanchnic nerve, including the splenic nerve [98][99][100][101][102][103] and adrenal nerve. [104] With that rationale, Galvani Bioelectronics recently initiated clinical trials in the US and UK, where a direct splenic nerve stimulation (rather than VNS) is being used to treat the RA.…”
Section: Anti-inflammatory Effects Of Bemmentioning
confidence: 99%
“…Recently, SNM has been shown to reduce intestinal inflammation in rodent models of inflammatory bowel diseases, suppress a number of proinflammatory cytokines including TNF, and enhance anti-inflammatory cytokines such as IL-10 in both intestinal tissues and in circulation ( 55 , 56 ). The anti-inflammatory effect of SNM on the colon is mediated via the spinal afferent and vagal efferent pathways evidenced by the following factors ( 57 ): (1) SNM activates neurons in the nucleus tractus solitaries ( 57 , 58 ); (2) SNM increases vagal efferent activity as assessed by the spectral analysis of heart rate variability and plasma level of pancreatic polypeptide ( 55 ); (3) bilateral subdiaphragmatic vagotomy almost completely abolishes the anti-inflammatory effect of SNM on the colon ( 57 ); and (4) SNM induces the release of acetylcholine in the colon ( 55 ). These findings suggest that SNM shares a similar vagal efferent pathway as VNS.…”
Section: Role Of the Nervous System In Immune And Respiratory Controlmentioning
confidence: 99%